2012
DOI: 10.1177/0149206311436079
|View full text |Cite
|
Sign up to set email alerts
|

What We Know and Don’t Know About Corporate Social Responsibility

Abstract: The authors review the corporate social responsibility (CSR) literature based on 588 journal articles and 102 books and book chapters. They offer a multilevel and multidisciplinary theoretical framework that synthesizes and integrates the literature at the institutional, organizational, and individual levels of analysis. The framework includes reactive and proactive predictors of CSR actions and policies and the outcomes of such actions and policies, which they classify as primarily affecting internal (i.e., i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

73
2,895
0
97

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 2,799 publications
(3,065 citation statements)
references
References 194 publications
(421 reference statements)
73
2,895
0
97
Order By: Relevance
“…Because of the socioeconomic transformations that many firms have undergone in recent years, corporate social responsibility (CSR) has attracted increasing interest in the business and academic spheres (Aguinis & Glavas, 2012;Waddock, 2004). Several broad-ranging conceptualizations of CSR BAR, Rio de Janeiro, v. 13, n. 4, art.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Because of the socioeconomic transformations that many firms have undergone in recent years, corporate social responsibility (CSR) has attracted increasing interest in the business and academic spheres (Aguinis & Glavas, 2012;Waddock, 2004). Several broad-ranging conceptualizations of CSR BAR, Rio de Janeiro, v. 13, n. 4, art.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides discussing how and when companies are socially responsible, scholars have also explored the impacts that social responsibility initiatives have on businesses themselves (Aguinis & Glavas, 2012;Campbell, 2007). Some have suggested that CSR can positively affect firms financially, by promoting improved relations with their stakeholders, thereby reducing transaction costs, production costs and certain associated risks (Barnett, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is clear that the individual level is crucial to the achievement of sustainability goals, current research in business and management literature mainly concentrates on factors affecting or enhancing sustainability performance emanating from the institutional and organisational level (see Aguinis and Glavas, 2012 for a review; Veldhuizen et al, 2013). There is a call for studies on the contribution of individuals that may affect organisational CSR-performance (Aguinis and Glavas, 2012). …”
Section: Introductionmentioning
confidence: 99%